Monitoring and modelling total phosphorus contributions to a freshwater lake with cage‐aquaculture. (3rd September 2015) - Milne, Jacquiline E; Marvin, Christopher H; Yerubandi, Ram; McCann, Kevin; Moccia, Richard D
Abstract: A mass‐balance modelling approach combined with a sensitivity analysis was utilized to gain an improved understanding of the relative contributions of phosphorus (P) loading from various anthropogenic and non‐anthropogenic sources into Lake Wolsey (Manitoulin Island, Ontario, Canada), a Type 2 freshwater lake with a cage‐aquaculture facility. Total P loadings were estimated from eight sources (inlet exchange, non‐point sources, cage‐aquaculture facility, internal loading, groundwater seepage, atmospheric deposition, leaf litter and dwellings) and three sinks (outlet exchange, sedimentation and sportfishing). Results indicated that over the study period (May–November 2007) the non‐point sources were the leading contributor of total P to Lake Wolsey (1120 kg P) followed by the cage‐aquaculture facility loading (915 kg P), inlet exchange (539 kg P), groundwater inputs (305 kg P), dwellings (219 kg P), internal P recycling loads from the hypoxic hypolimnion (186 kg P), atmospheric deposition (79 kg P) and decomposing leaf litter (8.1 kg P). When comparing the loadings in this study, the sensitivity analysis showed that non‐point sources were the only significant input parameter of total P loading to the in‐lake concentrations of P in Lake Wolsey( P = 0.05). Information from this project will provide water quality managers with sound scientific information to make defencible decisions pertaining to policy and regulatory approaches for water quality risk assessment and management of cage‐aquaculture in Type 2 sites.